2015
DOI: 10.3928/01484834-20151110-02
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Education in Health Professions Schools: An Integrative Review

Abstract: Background: Most Americans lack the health literacy skills to function in today's health care environment. The Institute of Medicine's Health Literacy: A Prescription to End Confusion report recommended that health professionals be trained to effectively communicate with patients with low health literacy. Method: An integrative review was conducted, using six electronic databases: CINAHL, ERIC, MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
6

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
3
32
0
6
Order By: Relevance
“…Indeed, the study showed health-care providers who had previous exposure to the term or concept of HL had significantly higher mean knowledge than no exposure (6.16 ± 1.67 vs. 5.68 ± 2.16, p = 0.028). Numerous other studies have supported the positive impact on improving providers’ knowledge and skills with the integration of HL component in the curriculum of health professional schools ( 24 26 ).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the study showed health-care providers who had previous exposure to the term or concept of HL had significantly higher mean knowledge than no exposure (6.16 ± 1.67 vs. 5.68 ± 2.16, p = 0.028). Numerous other studies have supported the positive impact on improving providers’ knowledge and skills with the integration of HL component in the curriculum of health professional schools ( 24 26 ).…”
Section: Discussionmentioning
confidence: 94%
“…HL training for HCPs increased their knowledge and awareness of patients´HL-related problems [40,41]. Recently, as part of an EU project, communication trainings focused on HL and designed specifically for HCPs in hospital settings were developed and successfully tested in the Netherlands, Ireland and Italy [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…training communication skills include didactic teaching, workshops, small-group activities, peer role play, videos, standardized patient encounters, observation, modeling, feedback, service learning, and online trainings (Institute for Healthcare Advancement, 2012; Coleman, 2011). More research into training methods is needed (Coleman, 2011;Toronto & Weatherford, 2015).…”
Section: Methods For Training Health Care Professionals In Teach Backmentioning
confidence: 99%